A novel tetra(μ3-phenoxo) bridged copper(II) Schiff base complex containing a Cu4O4 cubane core: Synthesis, structural aspects and magneto-structural correlations - Chakraborty, Joy; Thakurta, Santarupa; Pilet, Guillaume; Luneau, Dominique; Mitra, Samiran (Polyhedron, 2009)
A novel tetranuclear complex. [Cu4L4] center dot Na center dot ClO4 (1) has been prepared from an interesting multidentate Schiff base ligand H2L resulting from the 1:1 condensation of 3-methoxysalicylaldehyde with benzhydrazide. The prepared complex has been characterized by elemental analysis, FT-IR, UV-Vis spectroscopy, electrochemical studies and single crystal X-ray diffraction analysis. The Cu4O4 cubane core consists of four mu(3)-phenoxo-bridged copper(II) atoms giving an approximately cubic array of alternating copper(II) and oxygen atoms. Magneto-structural correlations have been drawn from cryomagnetic susceptibility measurements over a wide range of temperature (2-300 K) under 0.5 T magnetic field. The measurements reveal both ferromagnetic and anti ferromagnetic interactions in a 2J model [J(11) = +13.6(4) cm(-1) and J(12) = -34.9(4) cm(-1)] which in turn results in an overall anti ferro magnetic behaviour of the magnetic system. (C) 2009 Elsevier Ltd. All rights reserved.